Paradigm of dialectical pluralism for in-depth understanding: insights from investigating ethical leadership in schools through convergent mixed methods research - Bhattarai, Prakash C. (Frontiers in Education, 2025)
This article shows how the paradigm of dialectical pluralism can be applied for a deeper understanding of a research issue by abstracting insights from post-positivist and constructivist paradigms and bringing their interaction for additional meaning-making. As an example, a mixed methods study on ethical leadership is presented. On the study, the qualitative and quantitative strands had similar findings that ethical leadership was rooted in schools in the form of care, justice, and critique. However, contradictions were observed to their extent, which were answered by dialoguing between the strands, and the process of dialogue generated additional meaning. This article contributes to the mixed methods research in education by presenting evidence that dialectical pluralism provides additional meaning in the process of integrating the strands.